Endoscopic Placement of Feeding Tubes - Gabor P Kandel (Canadian Journal of Gastroenterology)
It is no exaggeration to say that percutaneous gastrostomy has revolutionized the feeding of disabled patients with intact gastrointestinal tracts. The most common indication is inability to swallow. It is generally best to place a gastrostomy tube early to prevent malnutrition and minimize complications of procedures on poorly nourished tissue. If a patient is expected to live for only weeks to months, nasoenteric feedings are the nutritional route of choice. Contraindications to percutaneous gastrostomy include coagulation disorders, upper gastrointestinal fistulas, intestinal obstruction, varices, peritoneal dialysis, septicemia and esophageal obstruction. Three techniques are described: 'pull,' 'push' and 'introducer.' The most frequently reported complications are wound infection and pneumoperitoneum. Now that multiple methods for successful insertion of endoscopic percutaneous feeding tubes have been described, the literature appears to be concentrating on complications of the various techniques. Nevertheless, compared to the other options available for patients unable to swallow (allowing malnutrition to proceed, tube feeding, surgical gastrostomy, parenteral nutrition), percutaneous gastrostomy is the procedure of choice in virtually all cases if the intestine is functioning.